Claude Bernard, machiniste du vivant - Fayolle, Azélie (Studia Romanica Posnaniensia, 2018)
Claude Bernard’s use of the metaphor of the “living machine” in his writings may seem surprising, since the theorist of experimental medicine is usually known for his disciplined stylistic and scientific rigor. An examination of the different occurrences of the word “machine” in a representative corpus of Claude Bernard’s writings shows that this phrase, which has a long history, allows for the identification of different scientific degrees in the physiologist’s work. This metaphor, which is also a thought pattern, emerges with the Introduction to the Study of experimental Medicine in 1865; its use indicates that some texts or textual zones are less scientific than they are philosophical or generalist.